Montages in the peri-urban palimpsest. Echographies for Leuven - Gerrits, Yuri; De Meulder, Bruno (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
This article delves into the debate on the peri-urban condition that surrounds Belgium’s cities and towns. It uses the case of Leuven as an example to unravel the territory’s unique though confusing structure that until this day remains largely tailored to its rural basis. This article moves in the slipstream of Corboz’ writing on “the land as a Palimpsest” and puts the focus on the intricate duality of vernacular and urban orders. More than relying on the ideals of postulated models, it explores the use of a method that seeks to rationalise the imperfection and alleged chaos, unveiling recurrent, emergent patterns of a hybrid order instead. A cartography of “Echographies” is proposed as a new tool to facilitate the indispensable deep reading and interpreting of the peri-urban condition. But it is also instrumentalised in support of a more customized approach of “architectural urbanism” that considers design as a continued transformation of what is already in place.